Performance Evaluation of Farm Machinery Utilization Under Custom Hiring Services Managements - Zulhanafiah, Zulhanafiah; Paman, Ujang (The University of Lampung, 2024)
Farm machinery hire service is a custom hiring business model managed by farmers’ groups at the farm level. The model is developed to facilitate access to farm machinery by small farmers and derive income (profit) from hiring out machinery services. This research attempts to evaluate the performance of farm machinery hire services in the Indragiri Hulu Region, Riau Province. The field surveys were conducted from September to October 2022 in 11 districts in the province. A total of 11 managers and 22 operators from 11 farm machinery hire service groups were selected purposively and interviewed to collect field data. The collected data were analyzed using descriptive and quantitative approaches. The results showed that farm machinery hire service groups manage 3 to 6 types of machines, including hand tractors, mini tractors, water pumps, rice transplanters, combine harvesters, and power threshers. The available farm machines are not sufficient to cover the entire area owned by farm machinery hire service groups. Therefore, most machines must work beyond capacity to achieve the target of covering as wide an area as possible. The machinery hire service was profitable for businesses at the farm level in the region. The results suggest that the number and type of farm machines must be added to increase the working area and make more profit. Keywords: Economic performance, Farm machinery hire services, Performance evaluation, Technical performance, Working area.